Structural behaviour of reinforced palm kernel shell foamed concrete beams - Alengaram, U.J.; Jumaat, Mohd Zamin; Mahmud, Hilmi (2009)
Experimental results of an investigation conducted to study the structural behaviour of reinforced palm kernel shell foamed concrete (PKSFC) beams prepared using palm kernel shell (PKS) as lightweight aggregates (LWA)are reported. The use offoam in the PKS concrete was to reduce the density ofPKS concrete from 1900 kg/rrr' to 1650 kg/m! and at the same time to produce grade 20 concrete using mineral admixtures. 10% silica fume and 5% class F fly ash were used as additional and cement replacement materials respectively in PKSFC, but normal weight concrete (NWC) contained none. The test results show that flexural and shear capacities of the PKSFC beams were found close to that of NWC beams. The PKSFC beams exhibited more cracks within the flexural zone and shear cracks in the shear zone than NWC beams. The deflection of PKSFC was found to be higher than that of NWC beams.